KEMAMPUAN GURU DALAM PENERAPAN KURIKULUM 2013 TERHADAP HASIL BELAJAR SISWA KELAS XII IPS PADA MATA PELAJARAN SOSIOLOGI DI SMA NEGERI 2 SIGI TAHUN PELAJARAN 2017/2018 - Anjurdin, Anjurdin; Suyuti, Suyuti; Nuraedah, Nuraedah (Katalogis, 2020)
This research aims to; (1) describe the ability of teachers in designing and evaluating learning through the 2013 curriculum in Class XII of SMA Negeri 2 Sigi; (2) knowing the ability of teachers to implement learning strategies through the 2013 curriculum in class XII of SMA Negeri 2 Sigi. 3) determine the impact of the implementation of the 2013 curriculum on student learning outcomes in class XII of SMA Negeri 2 Sigi. Data collection techniques namely observation, interviews and documentation. Data analysis techniques using qualitative analysis. The results obtained are: 1) The ability of teachers in designing planning for the implementation of the 2013 curriculum at SMAN 2 Sigi, teachers are able to link basic competencies, learning materials, learning activities, indicators of competency achievement, assessment, learning resources and the application of information and communication technology that they design in one wholeness learning experience. 2) the ability of teachers to implement learning strategies through the 2013 curriculum using direct learning strategies and indirect learning strategies. 3) the impact of applying the 2013 curriculum to student learning outcomes is the value of student semester exam results on average by more than 70%, this is because teachers use scientific approach models, project based learning, discovery learning, and various forms of strategies to improve student learning outcomes.